Creativity between nihilism and the search for meaning: Zeitgeist and creative innovation in body art - Jerrentrup, Maja (Creativity Studies, 2025)
A recent tattoo style, the sticker sleeve, brings with it some peculiarities: for example, unlike other styles, the focus seems to be less on originality or artistry. Further, the motifs integrated often imply almost incompatible messages, from spirituality and the search for meaning to the denial of meaning. Based on content analysis and interviews, the article explores what this style reveals about creativity and the Zeitgeist. One can interpret this in the tradition of nihilism as a denial of meaning or as a general instead of concrete concept of meaningfulness. Furthermore, it can be seen as a symbol for a creative way of dealing with cognitive dissonance. A complicated relationship to individuality is articulated, on the one hand the overcoming of the desire for unconditional individuality in favor of the recognition of shared human features, on the other hand the call to look behind the surface and recognize individual meanings behind shared looks.